2002
DOI: 10.1002/pen.10982
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of induction time and crystallization rate for syndiotactic polystyrene

Abstract: One objective of this study was to measure the crystalkation parameters for syndiotactic polystyrene (M, = 244,000) to support a computer simulation of this material in an injection molding application. A second objective was to introduce a new crystallization rate equation that adequately predicts crystallization rates over a broader temperature range than the Hofhnan-Lauritzen equation. A third objective was to establish a new clearly defined method for determining the true induction time of a semicrystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Also indicated in Figure 3 are experimental results for T 1/2 versus φ from five sources in the literature,4, 7–10 as documented in Table II. In particular, it is noted that the nine data points (Δ) from Chiu et al9 agree extremely well with the solid curve in Figure 3, with an rms deviation of 0.5°C over the extensive cooling‐rate range of 1 to 80°C/min.…”
Section: Constant‐cooling‐rate Crystallization Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also indicated in Figure 3 are experimental results for T 1/2 versus φ from five sources in the literature,4, 7–10 as documented in Table II. In particular, it is noted that the nine data points (Δ) from Chiu et al9 agree extremely well with the solid curve in Figure 3, with an rms deviation of 0.5°C over the extensive cooling‐rate range of 1 to 80°C/min.…”
Section: Constant‐cooling‐rate Crystallization Resultsmentioning
confidence: 99%
“…In addressing the above discrepancy, it is noted that of the five experimental investigations4, 7–10 reported in Figure 3, only Chiu et al9 corrected their data for the effects of thermal lag. Although results for their own experimentally determined thermal–lag correction are not explicitly presented by Chiu et al,9 one might refer to earlier work by Monasse and Haudin,18 dealing with polypropylene, in which the thermal–lag correction was determined experimentally and fitted with a linear dependence upon cooling rate, namely According to this result, the actual specimen temperature would be higher than the instrument reading by 1.07°C at φ = 10°C/min and by 10.7°C at φ = 100°C/min.…”
Section: Constant‐cooling‐rate Crystallization Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…New polymer materials with remarkable properties, such as high glass‐transition temperatures ( T g 's), high melting temperatures ( T m 's), heat resistance, chemical resistance to common solvents, low moisture uptake, high water barriers, good mechanical properties, and transparency, are traditional objects of basic and applied material science. Syndiotactic polystyrene (sPS) is a semicrystalline polymer that attracts much attention1–8 because of its high T m (≅285°C), rapid crystallization, and high crystallinity and modulus; on the other hand, its T g (≅100°C) is approximately equal to that of atactic polystyrene (PS). Mainly, the heat resistance and chemical stability allow potential applications of sPS at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly, the heat resistance and chemical stability allow potential applications of sPS at elevated temperatures. The crystalline phase of sPS has been the subject of many studies,1–8 which have shown the coexistence of several crystalline modifications (polymorphism), although under ordinary conditions, the α modification (a planar all‐trans form with a planar zigzag backbone structure) dominates 3. The stiffness of crystalline sPS has been ascribed to intrachain interactions involving bond bending and stretching.…”
Section: Introductionmentioning
confidence: 99%